2017
DOI: 10.1016/j.prnil.2017.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen and D-dimer levels in prostate cancer: Preliminary results

Abstract: BackgroundProstate cancer is one of the most common malignancy in men. The main risk factors for coagulation activation and thrombosis are malignancy and older age. The thrombosis risk may be associated with increased level of coagulation markers such as fibrinogen and D-dimer. The aim of this study is evaluate the relationship between coagulation markers and prostate cancer.MethodsThis prospective study includes the patients who underwent transrectal ultrasound guided prostate biopsy and prostate surgery was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…D-dimer can be easily diffused into the bloodstream due to their low molecular weight. This conception can be supported by elevated D-dimer levels that are found in cancer or acute inflammatory patients [ 5 , 6 ]. Previous studies found that while D-dimer has a high negative predictive value for excluding DVT and PE, the positive predictive value for DVT and/or PE is very poor.…”
Section: Discussionmentioning
confidence: 99%
“…D-dimer can be easily diffused into the bloodstream due to their low molecular weight. This conception can be supported by elevated D-dimer levels that are found in cancer or acute inflammatory patients [ 5 , 6 ]. Previous studies found that while D-dimer has a high negative predictive value for excluding DVT and PE, the positive predictive value for DVT and/or PE is very poor.…”
Section: Discussionmentioning
confidence: 99%
“…As an acute-phase protein, Fib increases during systemic inflammation, trauma, surgery, blood vessel thromboembolism, and cancer progression [ 12 ]. Previous studies claimed that high plasma Fib was associated with tumor aggression and poor prognosis in multiple kinds of cancers [ 13 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Plasma D-dimer is the product of cross-linked fibrin degradation by plasmin-induced fibrinolytic activity, and this marker has been widely used as a useful indicator of hemostasis and fibrinolysis activation. Elevated preoperative plasma D-dimer levels have been reported to be an unfavorable prognostic factor in various malignancies, such as lung cancers, 6,15 digestive tract cancers, 16 urological cancers 10,11,17 and soft tissue sarcomas. 5,7 The mechanism underlying the association between elevated plasma D-dimer levels and malignancy remains speculative.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated plasma D-dimer levels may be associated with disseminated intravascular coagulation, pregnancy, infectious diseases, trauma, surgery, and venous thromboembolism. 8 Although elevated circulating D-dimer levels are related to various cancers, such as lung, breast, prostate, and bladder cancer, 6,[9][10][11] the relationship between this hemostatic biomarker and UTUC survival outcomes is unclear. Therefore, the purpose of the current study was to investigate the prognostic value of preoperative plasma D-dimer levels in UTUC.…”
Section: Introductionmentioning
confidence: 99%